Low quality as a signal of high quality - Matthew T. Clements (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
If a product has two dimensions of quality, one observable and one not, a firm can use observable quality as a signal of unobservable quality. The correlation between consumers' valuation of high quality in each dimension is a key determinant of the feasibility of such signaling. A firm may use price alone as a signal, or price and quality together. Both signals tend to be used when the market is very uninformed, whereas price signaling alone tends to be used when the market is moderately informed. If high observable quality is inexpensive to provide, then it cannot signal high unobservable quality, and low observable quality is always an indication that unobservable quality is high.
Keywords: D82; L15; 330; Signaling; quality; Produktqualität; Signalling; Betriebliche Preispolitik; Konsumentenverhalten; Informationsverhalten; Theorie